Pengaruh Budaya Organisasi, Kompetensi dan Motivasi Terhadap Kinerja Guru Madrasah Ibtidaiyah di Polewali Mandar - Ramadhan L; Rina; Hafipah (Jurnal Online Manajemen ELPEI, 2023)
The aims of this study were 1) to analyze the effect of organizational culture on the performance of Madrasah Ibtidaiyah teachers in Polewali Mandar, 2) to analyze the influence of competence on the performance of Madrasah Ibtidaiyah teachers in Polewali Mandar, 3) to analyze the effect of motivation on the performance of Madrasah Ibtidaiyah teachers in Polewali Mandar, and 4) To analyze simultaneously the influence of organizational culture, competence and motivation on the performance of Madrasah Ibtidaiyah teachers at Polewali Mandar. The analytical method used in this study is the Multiple Regression analysis method. The research data were obtained from 50 Madrasah Ibtidaiyah teachers in Polewali Mandar. The research approach is a causal approach that is explanatory in nature. The results of this study indicate that: 1) Organizational culture has a positive and significant effect on teacher performance at Madrasah Ibtidaiyah at Polewali Mandar, this shows that the better the organizational culture, the better it will affect teacher performance, 2) Competence has a positive and significant effect on teacher performance at Madrasah Ibtidaiyah at Polewali Mandar, this shows that the higher the competence, the better the effect on teacher performance, 3) Motivation has a positive and significant effect on teacher performance at Madrasah Ibtidaiyah at Polewali Mandar, this shows that the higher the motivation teacher work, it will also have a good effect on teacher performance, and 4) Organizational culture, competence and motivation simultaneously have a positive and significant effect on teacher performance at Madrasah Ibtidaiyah in Polewali Mandar, this shows that the better organizational culture, competence and work motivation teacher, then ak It also has a good effect on teacher performance.